2017
DOI: 10.1021/acsnano.7b00597
|View full text |Cite
|
Sign up to set email alerts
|

Structure Controlled Long-Range Sequential Tunneling in Carbon-Based Molecular Junctions

Abstract: Carbon-based molecular junctions consisting of aromatic oligomers between conducting sp hybridized carbon electrodes exhibit structure-dependent current densities (J) when the molecular layer thickness (d) exceeds ∼5 nm. All four of the molecular structures examined exhibit an unusual, nonlinear ln J vs bias voltage (V) dependence which is not expected for conventional coherent tunneling or activated hopping mechanisms. All molecules exhibit a weak temperature dependence, with J increasing typically by a facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(127 citation statements)
references
References 57 publications
27
100
0
Order By: Relevance
“…Figure D displays the average JV behavior collected under vacuum of the four MJ structures in the present study with the observed RR values ( RR  | J −3.5 V / J +3.5 V |) of the bilayer MJs. All JV curves were observed to be similar to those previously reported, independent of scan rate in the bias region studied, and stable for at least thousands of JV scans. The bilayer JV curves require larger applied bias to achieve current densities similar to the single‐layer MJs due mainly to increased thickness.…”
Section: Summary Of Voc and Jsc Values Measured With A 407 Nm Laser Isupporting
confidence: 84%
See 2 more Smart Citations
“…Figure D displays the average JV behavior collected under vacuum of the four MJ structures in the present study with the observed RR values ( RR  | J −3.5 V / J +3.5 V |) of the bilayer MJs. All JV curves were observed to be similar to those previously reported, independent of scan rate in the bias region studied, and stable for at least thousands of JV scans. The bilayer JV curves require larger applied bias to achieve current densities similar to the single‐layer MJs due mainly to increased thickness.…”
Section: Summary Of Voc and Jsc Values Measured With A 407 Nm Laser Isupporting
confidence: 84%
“…Proposed mechanism of charge transport through C) BTB or D) AQ excitation. Energy levels were determined from DFT and do not include level shifts by electronic coupling with the contacts[11b] or between the AQ and BTB layers.…”
Section: Summary Of Voc and Jsc Values Measured With A 407 Nm Laser Imentioning
confidence: 99%
See 1 more Smart Citation
“…36 However, the minor changes in the UV−vis spectrum with increasing layer thickness implies relative weak coupling between molecular subunits, and a limited conjugation length within the interior layer. 6 The main question in the current report is a correlation of the absorption and PC spectra, to determine the origin of PC generation. Figure 3 shows overlays of the absorption and PC spectra for FL, AQ, NAB, and NDI, and additional examples are provided in Figures S5−S12.…”
Section: ■ Resultsmentioning
confidence: 98%
“…We concluded that transport was by multistep tunneling through the H−L barrier in the interior of the MJ, and the smaller barriers at the electrode interfaces were not controlling the current. 6 We proposed that the tunneling barriers are likely located between the molecular subunits, where the electronic interactions between subunits of the molecular layer are weak and delocalization length is limited to one or at most two attached molecules. The direct correlation between optical absorption and PC implies that photon absorption permits carriers to traverse the H−L tunneling barrier and result in measurable PC under illumination.…”
Section: ■ Discussionmentioning
confidence: 99%